2005
DOI: 10.1159/000089346
|View full text |Cite
|
Sign up to set email alerts
|

Mikro- und Nanosystemtechnik – medizintechnologische Aspekte am Beispiel eines Blasendrucksensors

Abstract: In der minimal invasiven Diagnostik, Therapie und Therapiekontrolle, bei Implantaten oder Medikamentdosiersystemen sind heute mikro- und nanotechnologische Komponenten wesentliche Bausteine von Gesamtsystemen. Aktuelle Entwicklungen zeigen ein weites Feld von Einsatzmöglichkeiten der Mikro- und Nanotechnik für medizinische Anwendungen. Allein der Weltmarkt physikalischer Sensoren für Druck, Temperatur und Beschleunigung erreichte im Jahr 2003 ein Handelsvolumen von mehreren 100 Milliarden EUR. Aufgrund extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…[12,25] Clasbrummel et al have independently proposed a similar wireless system as described in this study. [15] Majerus et al have also reported their work on a pressure sensor for submucosal implantation with wireless battery recharging. [14,26] In this study, we have demonstrated the feasibility of wireless induction in vivo for pressure measurement using a catheterless device in the bladder lumen for both power and real-time data communications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12,25] Clasbrummel et al have independently proposed a similar wireless system as described in this study. [15] Majerus et al have also reported their work on a pressure sensor for submucosal implantation with wireless battery recharging. [14,26] In this study, we have demonstrated the feasibility of wireless induction in vivo for pressure measurement using a catheterless device in the bladder lumen for both power and real-time data communications.…”
Section: Discussionmentioning
confidence: 99%
“…Several implantable devices based on pressure microsensors have been proposed as alternative to catheters. [1115] Key features of these devices are data readout and power supply which both contribute to the device dimensions. Other problems in common with catheters are the insertion methods and intravesical retainment mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Clasbrummel and Muhr [5] suggested suturing the system inside the bladder; other systems are large enough that expulsion is impossible, but they are not installable through a cystoscope. Some authors have not provided any information how to prevent an expulsion [9].…”
Section: Discussionmentioning
confidence: 99%
“…The catheterless pressure measurement is generally of great interest for many medical applications such as intracranial pressure measurement [3] or real-time blood pressure measurement [4]. Some devices have been designed especially for the intravesical pressure measurement [5][6][7][8]. Implantable measurement systems have to be very small, so that the power supply is one of the most crucial topics.…”
Section: Catheterless Pressure Measurementmentioning
confidence: 99%
“…It has to be ensured that the system is not expulsed from of the bladder during micturition. Clasbrummel [7] suggested suturing the system inside the bladder, other systems are too large so that an expulsion is impossible [6], but they are not implantable through a cystoscope. Some authors give no information how to prevent an expulsion [8].…”
Section: Catheterless Pressure Measurementmentioning
confidence: 99%